Major challenges to the liberalization of the Turkish natural gas market - Akcollu, F (Oxford Institute for Energy Studies, 2006)
The Turkish gas market is one of the most rapidly growing – and is therefore becoming one of the most important – markets in Europe. However, during the 2000s it experienced setbacks in terms of anticipated demand growth and the anticipated development of liberalisation and competition. Plans for rapid liberalisation and reducing the market share of Botas encountered harsh practicalities and legal obligations in relation to long term contracts signed with external suppliers. This paper sets out these problems and fills a gap in the gas literature not simply in relation to recent developments in the Turkish gas market, but also the perils of trying to introduce an unrealistically ambitious timetable for liberalisation in an emerging gas market. This is the OIES the Gas Research Programme's third publication on Europe’s major gas markets published this year, following Philip Wright’s book on the UK and Heiko Lohmann's study on Germany.